The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1471-0528.2004.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy in a woman with an increased body mass index

Abstract: Objective To show the increased risk of adverse outcomes in labour and fetomaternal morbidity in obese women (BMI > 30). Design A population-based observational study.Setting University Hospital of Wales. The study sample was drawn from the Cardiff Births Survey, a population-based database comprising of a total of 60,167 deliveries in the South Glamorgan area between 1990 and 1999. Population Primigravid women with a singleton uncomplicated pregnancy with cephalic presentation of 37 or more weeks of gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
149
6
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(195 citation statements)
references
References 19 publications
30
149
6
6
Order By: Relevance
“…Maternal pregnancy BMI did not significantly contribute to the birth weight of neonates in current study. Similar observation was made by researchers elsewhere (UshaKiran et al, 2005). Many colleagues have also argued that neonatal birth weight is favored greatly to a point of having macrosomic neonates in obese mothers mostly (Brennand et al, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…Maternal pregnancy BMI did not significantly contribute to the birth weight of neonates in current study. Similar observation was made by researchers elsewhere (UshaKiran et al, 2005). Many colleagues have also argued that neonatal birth weight is favored greatly to a point of having macrosomic neonates in obese mothers mostly (Brennand et al, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…The present study observed that the rate of caesarean delivery was more in the women with waist circumference ≥ 80 cm and this was found in concordance with that of Verma and Shrimaili, 3 Addo VN 17 , Burstein et al [20] (32.9% in obese, 9% in non-obese), Usha Kiran et al [16] (27% of obese women, 18% of non-obese women). Out of the vaginal births, 4.7% in group I and 11.5% in group II required instrumentation with either forceps or vacuum in the present study and was statistically insignificant.…”
Section: Discussionsupporting
confidence: 80%
“…Usha Kiran et al [16] reported <7 APGAR score at 5 min in 0.9% neonates of non-obese women and in 1.2% neonates of obese women. Bhattacharya et al [11] also reported higher stillbirth rates in the obese (1.9%) as compared to normal BMI categories (0.9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations